HUBUNGAN BENTUK LAHAN DAN TANAH MELALUI PENDEKATAN BENTUKLAHAN.SECARA FAKTORIAL = SOIL AND LAN DFORM RELATIONSHIPS THROUGH FACTORIAL LANDFORM APPROACH - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
An efficient yet scientifically accepted soil mapping method is in need. For this purpose, the research is intended: to identify landform units in the study area, and to give a quantitative evidence for the relationships between landform, slope, landuse units and soil units in the study area through spatial modelling. Step-wise methode has been applied to prove the relationships between the distribution of soil units and landform, slope. landuse units through the measurement of Lambda value (relative decrease of error probability) in every step. The results show that there is an increment of Lambda value by the more parameter applied for mapping unit construction. Lambda value is 72,5% for landform units as mapping unit, 82,4% for landform and slope units as mapping unit, and 88,2% for landform, slope, and landuse units as mapping unit. The conclusions of the research is soil mapping by applying geomorphological analysis and RS and GIS techniques may not require an intensive field check anymore. Therefore, the budget and time consumption for soil mapping may be reduced significantly. Key words: landform, soil, remote sensing, geographic information systems